Self-care Behaviors and Influential Factors among Nurses Working in the Hospitals of Tehran - Batoul Ahmadi; Hosein Rafiemanesh; Reza Shamlou; Yones Kor; Mozhgan Letafat Nezhad; Mojtaba Mehtarpour (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Nurses' self-care assessment and elimination of obstacles with appropriate interventions will have a great impact on their own health as well as the recipients of health services. This study was designed to evaluate self-care status among nurses in selected hospitals in Tehran, Iran. Methods: This cross-sectional study was carried out on 310 nurses working in Tehran University of Medical Sciences hospitals. Data were collected by a questionnaire with 70 questions that was conducted to evaluate the health level in five dimensions. Data were analyzed by using the statistical tests of MANOVA and Pearson's correlation. Results: The average scores of nurses' self-care in men and women were 244.1 and 245.3, respectively. The highest average score was for the supportive relationships dimension. There was a significant relationship between gender and self-care dimensions (P-value = 0.077). The average scores of self-care for nurses working in the emergency department, general department, surgical department, intensive care unit, and other sectors were 238.5, 247, 240.6, 245.6 and 251.1, respectively. There was a positive relation between supportive relationships dimension, age, and years of employment. In addition, there was a negative relation between the number of children and supportive relationships dimension (P-value < 0.05). Conclusion: This study showed that self-care among nurses in the hospitals of Tehran University of Medical Sciences was moderately high, in a good and acceptable situation. However, there were poor scores in some areas and further study of the nurses' self-care and its promoting strategies is still required.